(untitled) (Global Journal of Human-Social Science, 2021)
This paper examines influence of good governance on coronavirus pandemic in Nigeria. The kernel of this article is the intrinsic nexus between good governance, bad governance and coronavirus pandemic in a democratic state. Multi-stage sampling procedure was employed in selecting respondents for the study. 209 of 230 respondents used for the study filled the questionnaire appropriately for the study. The finding of the study shows that that there was a positive significant relationship between governance and health information (r = .581**, N= 219, P < .05); citizen and good governance (r = .485**, N= 219, P < .05) and good governance and the management of Coronavirus pandemic (r = .431**, N= 219, P < .05). It therefore shows that there is a need for Government to gain trust among the populace in order to build a policy that will enhance and promote the mitigation of Coronavirus pandemic in Nigeria.